DDIS-23. CMV-BASED PLASMID DNA VACCINE FOR GBM USING THE UNITE PLATFORM. (11th November 2019) - Adhikari, Amit; Toll, Barb; Johnson, Yoshimi; Marketon, Anthony; Wilson, Greg; Macauley, Juliete; Heiland, Teri
Abstract: Glioblastoma (GBM) is an aggressive form of brain cancer with a median survival of 15 months, remaining unchanged in spite of technological advances in the standard of care. The presence of the partial CMV genome, specifically in GBM cells, provides a great opportunity for a targeted therapy. We have utilized our UNITE (UNiversal Intracellular Targeted Expression) platform to build a polyvalent DNA vaccine which includes HCMV proteins, pp65, gB and IE-1. The UNITE platform is based, in part, on a lysosomal targeting technology which can result in increased antigen presentation, a balanced T cell response, and subsequent immunologic benefit. Using an orthotopic GBM mouse model expressing CMV proteins in the CT2A cell line, we have shown up to 45% survival when treated therapeutically with the pp65-IE-1 vaccine. In order to further improve the vaccine's efficacy, and also to understand the mechanism of action, we are evaluating the post-vaccination tumor microenvironment and testing combination therapies with immune checkpoint inhibitors. Preliminary data on treated tumors suggest an increase in the PD-1 immune checkpoint regulator and a higher number of regulatory T cells. Our immune response evaluation of the polyvalent vaccine in naïve mice showed generation of robust antigen specific T cell activation. The use of multiple antigens in this vaccine makes it better suited to prevent antigen escape by tumor cells. Encouraged by our non-clinical data and the promising outcomes from our collaborators' clinical trials using pp65 mRNA transfected autologous dendritic cells (ATTAC and ATTAC-II), we are moving forward with a phase I trial. We believe that the immune boost from our UNITE platform combined with deactivation of the immunosuppressive microenvironment by checkpoint inhibition holds a promising treatment against GBM.